A retrospective study of the epidemiological characteristics of patients with orofacial clefts: Craniofacial anomalies unit of the University Hospital of Maracaibo - Nicolás E Solano; Manuel Alejandro Linares; Jondalys López; Mariela Fox; Luis Sarmientos; Blanca Álvarez (Wolters Kluwer Medknow Publications, 2020)
Aims: The aim of this study was to describe the epidemiological characteristics of patients with orofacial clefts attended at the Craniofacial and Cleft Surgery Unit of the University Hospital of Maracaibo. Settings and Design: This was a retrospective, epidemiological, cross-sectional study. Subjects and Methods: The sample was constituted by clinical histories of patients with orofacial clefts attended in the Craniofacial Surgery and Clefts Unit of the University Hospital of Maracaibo from September 2015 to March 2018. Demographic data of the patient, family history, anatomical structures involved in the cleft and syndromic association. were collected, and analyzed in accordance with the type of research and the objectives set, a descriptive analysis of each variable was performed, represented by absolute and relative frequency. Results: There were 137 patients with cleft lip and/or palate in the unit, with an average age of 5.3 ± 9.8 years, evidencing an almost equitable distribution in relation to gender. Of the facial clefts, the most common was cleft palate (CP), followed by cleft lip and palate. A low incidence of the presence of craniofacial anomalies was observed in the family history and the syndromic association. Conclusions: It was observed that the prevalence of cleft lip and CP has increased in recent years; these epidemiological figures vary by region, age, and gender. However, a greater knowledge on the part of health professionals is necessary to understand the clinical and epidemiological aspects of orofacial cleft and is crucial to improve the understanding of pathogenesis, promote preventive strategies, and guide multidisciplinary clinical care.